Comparative social network analysis in a leaf-roosting bat - Chaverri Echandi, Gloriana (2010)
Even though social network analysis provides an important tool to characterize and compare societies, no studies have used its analytical applications to characterize patterns of sociality in bats. Here I use social network analysis to characterize and compare patterns of sociality between three populations of the leaf-roosting bat Thyroptera tricolor. Sites differed in the density of furled leaves used by T. tricolor for roosting. Finca had more leaves per hectare (77), followed by Ureña (58), and Esquinas (7). The time period over which the probability of association is halved based on fitted models was 1,086 days for Finca, 714 days for Ureña, and 303 days for Esquinas. Finca and Ureña had very similar network topologies, with several small clusters, high-clustering coefficients, short path lengths, low node betweenness, and high network robustness. Social networks at Esquinas were composed of one large cluster and several small isolated ones. Esquinas also had high-clustering coefficients, but path length and node betweenness were high. Network resilience was lower in Esquinas compared to Finca and Ureña. These results show that, unlike many other forest-dwelling bats that switch roosts regularly, T. tricolor does not exhibit a typical fission–fusion social system, and that resource availability seems to affect social networks in this bat. In addition, this study highlights the importance of emigrating individuals in maintaining social cohesion, establishing network connectedness, and determining network robustness.